Pengaruh Firm Size, OPM dan DER terhadap PER Industri Produk Makanan Pertanian - Angelina, Heppy; Elizabeth, Sri Megawati (MDP Student Conference, 2025)
This study aims to examine how various factors can affect the Price Earning Ratio in agricultural food product industry companies listed on the Indonesia Stock Exchange during the 2019-2023 period. The factors analyzed include Firm Size, Operating Profit Margin, and Debt to Equity Ratio. The sample of this study consisted of 28 listed companies, out of a total of 53 companies listed in the five-year period. The method used is an associative quantitative approach, which aims to identify relationships between variables and significant patterns. The results showed that Firm Size and OPM have a positive impact on PER, which means that the larger the company and the higher the OPM, the company's PER value tends to increase. Meanwhile, DER has no significant effect on PER. Overall, although some variables do not have a large effect, the three factors analyzed still affect the price-to-earnings ratio (PER) of the companies studied.